2016
DOI: 10.1614/ipsm-d-16-00005.1
|View full text |Cite
|
Sign up to set email alerts
|

Physical Control of Nonindigenous Aquatic Plants in Emerald Bay, Lake Tahoe, CA

Abstract: Establishment of nonindigenous (NI) aquatic plants in the nearshore regions of freshwater ecosystems has resulted in environmental degradation, recreation concerns, economic impacts, and substantial management challenges. To reduce these undesirable effects, NI aquatic plants are often targeted for removal or control by management agencies, but the efficacy of implementation is often not documented or sustained. In this study, we developed a management plan to completely remove all NI plants from Emerald Bay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The same process was repeated in 2021 from May 21 to June 1 (435 accumulated degree days >0 C by May 21), at the same locations, although the quadrat may have settled in slightly offset locations between 2020 and 2021. Stem density data collected in 2021 were compared with those of 2020 with paired-sample Wilcoxon signed-rank tests, because the data were not normally distributed (Scherrer 1984).…”
Section: Monitoring the Efficacy Of Myriophyllum Spicatum Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The same process was repeated in 2021 from May 21 to June 1 (435 accumulated degree days >0 C by May 21), at the same locations, although the quadrat may have settled in slightly offset locations between 2020 and 2021. Stem density data collected in 2021 were compared with those of 2020 with paired-sample Wilcoxon signed-rank tests, because the data were not normally distributed (Scherrer 1984).…”
Section: Monitoring the Efficacy Of Myriophyllum Spicatum Controlmentioning
confidence: 99%
“…In 2018, for example, monitoring resulted in the rapid detection and removal of 60 M. spicatum individuals, even though no specimen had been detected in the previous 4 yr (Hauge Brueck Associates, LLC 2020). The main conclusions of Shaw et al (2016) are (1) a large initial investment is required, (2) costs decrease over time if the initial stage is successful and followed by annual monitoring, (3) physical techniques can reduce the biomass of an invasive plant relatively quickly if adequate effort is made, and (4) focusing control efforts on a small number of sites is more effective than thinly stretching resources over a broad area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated regime for invasive plant control is a treatment in which one control method is followed by another. An increasing number of recent studies have shown that an integrated regime has higher control efficacy than a single method (Hammond 2001;Hedge et al 2003;Patten 2002Patten , 2003Roberts and Pullin 2007;Shaw et al 2016;Strong and Ayres 2016;Wang et al 2006). For example, some studies have found that mowing followed by application of glyphosate can inhibit the growth and infestation of invasive species of the genus Spartina (cordgrass), more than when either method is used alone (Hedge et al 2003;Patten 2002Patten , 2003Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The high control efficacy of an integrated regime is believed to occur because such regimes incorporate dual treatments (Hammond 2001;Hedge et al 2003;Shaw et al 2016;Wang et al 2006). However, while many studies have indicated the importance of different types of methods on the control efficacy of an integrated regime, the effects of the intensity of an integrated regime and the interval between the applied methods have been mostly ignored and are still unclear.…”
Section: Introductionmentioning
confidence: 99%